Professor orientador de estágio curricular da área da saúde: trajetória profissional e modos de atuação - Roveda, Patrícia Oliveira (2019)
This investigation is associated to the Training, Knowledge and Professional Development Research Line of Post-Graduate Program in Education of Universidade Federal de Santa Maria/RS. The research has as focus the professional career and the teaching action ways of supervisor - professors in the supervised curricular internships in health area. This thesis was guided by the objective of determining the relation between the professional trajectory and the configuration of the supervised internships in the ways of teaching action. It is a research with qualitative approach of narrative line (CLANDININ; CONNELY, 2015; CONNELLY; CLANDININ, 1995). A research path involved, firstly, the recognition of the documental repertoire of legislation about the supervised internship in undergraduate courses in health and the courses of health of a Public Institution of the South of Brazil / UFSM, articulated with the state of art, of knowledge and theoretical support of the areas of knowledge: education and health. We use the semi-structured individual narrative interview which represents the perception of the professor followed by the discursive textual analysis, translating the perception of the researchers about the narratives. 20 professors that are supervisors of curricular internships of the courses of nursing, pharmacy, physiotherapy, phonoaudiology, medicine, odontology and occupational therapy participated of the study. In a second moment, by means of an analysis and interpretation of findings, we organized and presented the results through three axes of analysis: Knowing the professional trajectory of supervising professors of internships; Conceptions about the curricular internships of supervisor-professors of internships and Living the daily practice: discoveries about the ways of teaching action in the supervised curricular internships. This organizing spectrum of the Thesis is intertwined to the creation of figures denominated mandalas, which represent the findings. The path taken allowed the researchers to identify that the ways of teaching action depend on the configuration of these internships and the professional trajectory of the professor. The narratives enabled a detailing of the routine in the internship and the ways of action, which vary with the different conceptions of internship of these professors. When they comprehend the internship as peak period of training in undergraduation shared with supervisors, the professors revealed the importance of their presence when monitoring the intern when doing the profession, opposite to what occurs when they conceive the internships as an autonomous pre-professional period in which the presence of the preceptor substitute the professor that remains as organizing functions. The professors did not carried out specific pedagogical training; however we noted a movement of self-training quite peculiar. The humanized inter-relation is rooted in the teaching performance in health and when considering the praxis in the supervised curricular internships we affirm that there is an inter-relational heptagon of health area. There is the imperative necessity of reflection on what the internship represents in graduation, once that there is an instituted problem in relation to what we understand as generalist profile, autonomy in training, functions of the supervisor-professor, as well as by the diversified interpretation of the law and by the relation services in health and training IES (Higher Institution). Considering the narrative of the professors that participate, two courses at all levels of attention maintain the supervisor-professor present in the fields of internship, giving pedagogical, theoretical, practical and relational support to the intern.